UJI KETAHANAN BEBERAPA VARIETAS DAN PENGARUH JARAK TANAM TERHADAP PENYAKIT KARAT DAUN (Puccinia polysora Underw) PADA TANAMAN JAGUNG (Zea mays L.) DI DATARAN RENDAH - Sukma Aditya; Hasanuddi Hasanuddi; Mukhtar Iskandar Pinem (Universitas Sumatera Utara, 2013)
Test of resistance of some varieties and the influence of planting distance on leaf rust(Puccinia polysora Underw.) on lowland. The aim of the research was to know the resistance ofsome varieties of corn (Zea mays L.) and the influence of planting distance on leaf rust(Puccinia polysora) on lowland. The research was conducted at Tanjung Selamat village, Medan.The research used Cluster Random Design of 2 factorials with 9 treatments and 3 repetitions. Theresults of the research showed that the varieties of BISI 13 were resistant to leaf rust of corn. Theoptimal treatment of planting distance for the attack of corn leaf rust was 70 x 25 centimeters. Theappropriate treatment of varieties and planting distance for the corn leaf rust attack was on V3J3treatment (BISI 13 with the planting distance of 70 x 25 centimeters). The highest corn productionof the varieties of BISI 13 was 6.3 tons/ha. The highest corn production of the planting distancetreatment of 70 x 25 centimeters was 5.58 tons/ha. The highest corn production in the interactiontreatment of BISI 13 with the planting distance of 70 x 25 centimeters was 7.54 tons/ha.Keywords: varieties of corn, planting distance, P. polysora, leaf rust, resistant varieties